Evaluation of in vitro release kinetics and mechanisms of curcumin-loaded cockle shell-derived calcium carbonate nanoparticles - Mailafiya, Maryam Muhammad; Abubakar, Kabeer; Danmaigoro, Abubakar; Chiroma, Samaila Musa; Abdul Rahim, Ezamin; Mohd Moklas, Mohamad Aris; Abu Bakar @ Zakaria, Md Zuki (BioMedPress, 2019)
Introduction: Curcumin has remarkable pharmacological activities but remains clinically constrained due to its poor bioavailability as a result of insolubility. This has necessitated the search for natural inorganic materials for curcumin delivery. Cockleshells are external hard materials of marine animals often treated as unwanted wastes, which are excellent sources of calcium carbonate. This study aimed to synthesize cockle shell-derived calcium carbonate (aragonite) nanoparticles (CSCaCO3NP) for delivery of curcumin and to evaluate its kinetic release in vitro. Methods: CSCaCO3NP was synthesized and conjugated with curcumin (Cur-CSCaCO3NP) using a simple top down approach and characterized for its physicochemical properties as a potential curcumin carrier. The in vitro release profile was assessed using the dialysis bag membrane method. The release data were fitted to Korsmeyer-Peppas, Zero order, and Higuchi models to evaluate the mechanism(s) of the release pattern. Results: A spherical shaped CSCaCO3NP with a surface area of 14.48+/-0.1 m2/g, with mean diameter size of 21.38+/-2.7 nm and zeta potential of -18.7 mV, was synthesized and found to have high loading content and encapsulation efficiency. The FT-IR and XRD revealed fewer observable changes on the peaks after conjugation. The profile of the in vitro kinetic release demonstrated a sustained release, and which was best fitted to the Higuchi equation model. Conclusion: The results of this study showed the capacity of the synthesized CSCaCO3NP to encapsulate curcumin efficiently with a stable release in vitro. This provides insight into and rationale for the potential of CSCaCO3NP for curcumin delivery. Therefore, CSCaCO3NP holds great prospects in the preclinical framework for enhancing curcumin efficacy in oral therapeutic applications.